Synthesis and Crystal Structure of Supramolecular Copper(II) Complex Based on N2O2 Coordination Sphere - Wang, P.; Zhao, L. (Asian Journal of Chemistry, 2015)
Copper(II) complex has been synthesized via the complexation of copper(II) acetate monohydrate with 4,6-dichloro-4',6'-dibromo-2,2'-[ethylenediyldioxybis(nitrilo-methylidyne)]diphenol (H2L) in acetone/acetonitrile solution and characterized structurally by X-ray diffraction method. X-Ray crystallographic analysis reveals that the Cu(II) atom is four-coodinated by the four atoms of the donor set (N1, N2, O3 and O4) in the asymmetic Salamo-type L2- unit and Cu(II) atom approximately lie in the same plane, resulting in an almost regular distorted square-planar geometry. Each Cu(II) complex molecule links two neighboring molecules into an infinite 1D chain supramolecular structure through intermolecular C1-H1B···O3, C1-H1A···Cl1 and C2-H2A···Br1 hydrogen-bonding interactions.